KESESUAIAN TEKNIS DAN OPERASIONAL PANGKALAN PENDARATAN IKAN DONGGALA DENGAN PERMEN-KP RI NOMOR PER.08/MEN/2012 TENTANG KEPELABUHANAN PERIKANAN - Aksa Azhari Aminullah; Mulyono Sumitro Baskoro; Mohammad Imron; Iin Solihin (Bogor Agricultural University, 2021)
Donggala fish landing centre is a fishery infrastructure of Donggala Regency provided for Mamuju Regency fishermen, West Sulawesi. Capture fisheries activities in PPI Donggala are incorporating various stages from landing to marketing. All capture fisheries activities are related to the PPI Donggala’s technical and operational condition. Some of purse seine fishing units did not land their catches at PPI Donggala which affect the performance of the fishing port. This study aims to identify the PPI Donggala’s technical and operational condition in compliance with PERMEN-KP RI NUMBER PER.08/MEN/2012 concerning Fisheries Ports. The research method is a case study conducted at PPI Donggala. Data were collected by interviews and literature studies, then analyzed using comparative descriptive method. The results of the study showed the technical and operational conformity of the port at PPI Donggala with PERMEN KP 08/2012 on Fisheries Port has met technical and operational criteria. However, there are still technical and operational constraints in PPI Donggala. The obstacle is that the pier is still damaged and the marketing of the catch has not been widespread. Keywords: PPI Donggala, technical aspects, operational aspects